Un nuevo plomo ibérico escrito de Monteró 1 (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Edition and commentary of a new Iberian lead tablet found in the site of Monteró 1 (Lleida).
Keywords: Monteró 1; Iberian Inscription; Lead; Epigraphy; Palaeohispanistic